Predictors of Teachers' Professional Development in Inclusive School - Nataša D. Tančić (University of Belgrade, Teacher Education Faculty, 2022)
Teachers' professional development is a complex and multi-faceted phenomenon that in recent decades, in many countries around the world, has been at the center of educational policy and become one of the central topics of scientific research aimed at improving the quality of educational work of modern - inclusive - school. The paper examines the professional development of teachers through the discourse of educational inclusion and current educational policies which intensively promote the right to quality education that best suits the child. The predictors of teachers' professional development in the model of an inclusive school are the topic of our research. The aim of the research was to determine the connection between a set of different factors - socio-demographic, personal, and contextual - with teachers' professional development and identify the determining factors among them. The research was conducted on a sample of 265 primary school teachers. Quantitative model, correlation design, and survey technique were used. The research results show that researching a wider range of factors was purposeful and indicate a different level of connection of the examined predictors with teachers' professional development. It has been determined that the predictors in the group of personal factors are central for the engagement and participation of teachers in professional development programs. In general, the research findings, with numerous new insights into the factors and limitations of teachers' professional development, contribute to building a more complete picture of the current practice of the professional development of teachers in inclusive school and are not only informative, but also useful to all actors in school practice, creators of educational policies in modeling and introducing changes in this area.